2018
DOI: 10.1038/s41598-018-29348-z
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmicity of Mood Symptoms in Individuals at Risk for Psychiatric Disorders

Abstract: Despite emerging evidence that disruption in circadian rhythms may contribute to the pathophysiology of psychiatric disorders, there is a significant knowledge gap on the rhythmicity of psychological symptoms. Here, we aimed at investigating the rhythmicity of mood symptoms in individuals at risk for psychiatric disorders. 391 Brazilian and 317 Spanish participants completed the Self-Reporting Questionnaire-20 for non-psychotic mental disorders; the Mood Rhythm Instrument was used to assess rhythmicity of mood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…Currently, extensive attention has been paid to the biological clock in the eld of psychiatry and psychology due to its importance. 6,[10][11][12]38,39 We hope that future research on optimizing the functions of the biological clock can develop a new area of "rhythmic medicine". If the circadian rhythm could be more effectively integrated with the warning, diagnosis and treatment of psychosomatic diseases, then, mental health might be improved, psychosomatic diseases prevented, and the therapeutic e cacy maximized.…”
Section: Synchronized Intervention Strategy For Rhythm Disruption Andmentioning
confidence: 99%
“…Currently, extensive attention has been paid to the biological clock in the eld of psychiatry and psychology due to its importance. 6,[10][11][12]38,39 We hope that future research on optimizing the functions of the biological clock can develop a new area of "rhythmic medicine". If the circadian rhythm could be more effectively integrated with the warning, diagnosis and treatment of psychosomatic diseases, then, mental health might be improved, psychosomatic diseases prevented, and the therapeutic e cacy maximized.…”
Section: Synchronized Intervention Strategy For Rhythm Disruption Andmentioning
confidence: 99%
“…Physiological stress is frequently associated with circadian disruption, and the regulation of the stress response system is one mechanism by which circadian rhythms are altered [91]. Thus, it is not surprising that disruptions in the circadian rhythms are a common symptom across stress-related psychiatric disorders [92]. Similar to the stress response system, the circadian clock is a well-conserved mechanism that allows organisms to adapt to their environment.…”
Section: Stress Response and Circadian Rhythmicitymentioning
confidence: 99%
“…The original version of this instrument was created in Brazilian Portuguese [21], which was then translated and validated in Spanish [22,23]. In a large study with 708 participants that completed the MRhI, we found that the rhythmicity of specific mood-related symptoms and behaviors, such as pessimism and motivation to exercise were associated with higher risk for psychiatric disorders [24]. Notably, we also found specific cultural differences in comparing Spanish and Brazilian samples in terms of the daily patterns of moodrelated symptoms [25].…”
Section: Introductionmentioning
confidence: 99%